Assessment of the inhibition risk of shikonin on cytochrome P450 via cocktail inhibition assay. (5th November 2017) - Tang, Shuowen; Chen, Ang; Zhou, Xiaojing; Zeng, Li; Liu, Mingyao; Wang, Xin
Graphical abstract: Highlights: The inhibition risk of shikonin on CYP enzymes was firstly investigated. Shikonin potently inhibited six CYP isoenzymes in both human and rat liver microsomes. Shikonin exhibited no time-dependent inhibition of CYP activities. Shikonin displayed different inhibition types on CYP isoenzymes. Abstract: Shikonin is a naphthoquinone pigment extracted from roots of Lithospermum erythrorhizon Sieb. et Zucc. (Boraginaceae), and possesses various pharmaceutical activities, such as anti-inflammation and anti-cancer effects. In addition, shikonin as a natural red colorant for food garnishment and cosmetics ingredient is widely used in the world. However, the inhibition risk of shikonin on cytochrome P450 (CYP) remains unclear. The aim of this study was to investigate the potential inhibition of shikonin against CYP1A2, CYP2B1/6, CYP2C9/11, CYP2D1/6, CYP2E1 and CYP3A2/4 activities in human and rat liver microsomes through cocktail approach in vitro. The results demonstrated that shikonin exhibited no time-dependent inhibition of CYP activities. In human liver microsomes, shikonin was not only a mixed inhibitor of CYP1A2, CYP2B6, CYP2C9, CYP2D6 and CYP3A4, but also a competitive inhibitor of CYP2E1, with K i values no more than 7.72 μM. In rat liver microsomes, shikonin also exhibited the mixed inhibition on CYP1A2, CYP2B1, CYP2C11, CYP2D1, and the competitive inhibition on CYP2E1. Interestingly, shikonin presented an atypical kinetic inhibition of CYP3A2-mediated midazolam 1-hydroxylation in rats. In conclusion, the relatively low K i values of shikonin would have a high risk potential to cause the possible toxicity, especially drug-drug or food-drug interactions based on the potent inhibition of CYP enzymes.